PEDOMAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA: PERAN INDEKS INTERNASIONAL - Handa Abidin (Faculty of Law - Tarumanagara University, 2018)
There are a number of positive impacts if Indonesia uses these three indexes: the World Bank’s Ease of Doing Business, the World Economic Forum’s Global Competitiveness Index, and the World Justice Project’s Rule of Law Index as guidance for “peraturan perundang-undangan” (laws and regulations). Nonetheless, it is important to note that there are also negative impacts that could arise. One of the important solutions to avoid negative impacts is to consistently comply with Pancasila and the 1945 Constitution of the State of the Republic of Indonesia. The concept of using international indexes as guidance is not only limited to the Ease of Doing Business, the Global Competitiveness Index, and the Rule of Law Index. Other relevant international indexes could have also roles in providing guidance for laws and regulations in Indonesia, by taking into account the discussion and recommendations in this research, in particular: these indexes must be in accordance with Pancasila and the 1945 Constitution of the State of the Republic of Indonesia. Furthermore, this research also provides recommendations for how to improve Indonesia’s rankings on the three indexes, which could also be relevant in the context of other international indexes.